Countering misogyny in the manosphere: Examining language, identity, and ideological confrontations in #MeToo narratives - Jegede, Olusegun Oladele (Englisia Journal, 2025)
This study investigates the ideological confrontations between #MeToo advocates and the manosphere, focusing on their competing visions of masculinity, accountability, and gender equality. It explores how these groups define and contest gender roles, particularly masculinity, and how their opposing ideologies shape contemporary gender discourse. The research objectives are to analyze contrasting perspectives on masculinity, evaluate debates over accountability, and examine differing interpretations of equality. Using a qualitative approach, the study applies critical discourse analysis to textual data from #MeToo and manosphere forums, social media posts, and key movement narratives. Findings indicate that #MeToo advocates promote empathy, equality, and respect to challenge traditional masculinity, while the manosphere defends a dominance-oriented view. #MeToo emphasises systemic accountability, in contrast to the manosphere’s focus on individual responsibility. The study concludes that this ideological conflict reflects a broader cultural struggle over gender norms and power dynamics, with #MeToo advocating for structural reform. Examining the dynamic relationship between #MeToo and the manosphere, this research offers novel insights into how they shape public perceptions of gender and inequality.